2015
DOI: 10.15288/jsad.2015.76.452
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Expectancies and Alcohol Outcomes: Effects of the Use of Protective Behavioral Strategies

Abstract: ABSTRACT. Objective: Alcohol expectancies (AEs) are positively associated with drinking behaviors, whereas the use of protective behavioral strategies (PBS) is negatively related to alcohol outcomes among young adults. PBS have been shown to weaken relationships between some alcohol risk factors and alcohol outcomes. This study aimed to examine longitudinally the moderating effect of PBS on the relationships between AEs and alcohol outcomes among young adults. Method: Participants (N = 188; 61.7% female) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
1
12
0
3
Order By: Relevance
“…Lastly, we have demonstrated that group size moderates the relationship between PBS and alcohol consumption. These findings provide additional support to consider PBS as a moderator in alcohol consumption [30,31]. Our findings have established an important framework on group composition.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Lastly, we have demonstrated that group size moderates the relationship between PBS and alcohol consumption. These findings provide additional support to consider PBS as a moderator in alcohol consumption [30,31]. Our findings have established an important framework on group composition.…”
Section: Discussionsupporting
confidence: 76%
“…To more formally investigate this issue, it would be important to know how physical health is distributed in adolescence by peer group and education. The negative consequences of binge drinking are well established, and PBS are regarded as a good way of reducing alcohol consumption or minimizing the risks associated with it [ 31 , 36 ]. In this sense, peer relationships can play a positive and protective role in coping with the adversities [ 26 ]; and young adults who share PBS can play a positive protector role in individual and group habits regarding alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children’s beliefs regarding positive or negative effects of alcohol are influenced by watching parental drinking, can develop in a short period of time, and can serve as predictors of their current and future drinking behaviours 23. Parental alcohol use or misuse is associated with subsequent alcohol consumption and misuse in adolescence through adulthood 456.…”
mentioning
confidence: 99%
“…A substantial body of cross-sectional research has established that the use of PBS is negatively related to alcohol use and alcohol-related consequences among young adults (i.e., college students; Araas & Adams, 2008;Benton et al, 2004;Delva et al, 2004;Martens et al, 2005;Martens et al, 2007;Pearson, 2013). Although less commonly evaluated in the literature, longitudinal research has reached similar findings, with greater use of PBS being generally related to less alcohol use Napper, Kenney, Lac, Lewis, & LaBrie, 2014) and fewer alcohol-related problems over time Grazioli, Lewis, et al, 2015;Luebbe, Varvel, & Dude, 2009;Napper et al, 2014). Further evidence for the association between the use of PBS and alcohol outcomes stems from clinical trials that found increase of PBS use following brief interventions (e.g., personalized mailed feedback) as a significant mechanism accounting for the intervention's effect on alcohol use (Barnett, Murphy, Colby, & Monti, 2007;Larimer et al, 2007), although results have not always been consistent across studies (Kulesza, Apperson, Larimer, & Copeland, 2010;Neighbors, Lee, Lewis, Fossos, & Walter, 2009;Reid & Carey, 2015).…”
Section: Introductionmentioning
confidence: 99%